(untitled) (Linguostylistic Studies, 2017)
The article considers the usage of phraseological units in the story «Cherry Nights» by Boris Kharchuk. The author suggests classification of the phrasiological set-expressions according to the semantic principle and presents their stylistic analysis. The study offers insights into the «phraseological» portraits of characters. Various in terms of semantics, structure and emotional saturation, phraseologisms and the variety of their stylistic and expressive functions have been revealed. Individual peculiarities of the use of phraseologisms in the literary works are considered in the article as a manifestation of the writer’s idiostyle: «phrases» convey imagery and emotionality in the expression of thoughts and ideas, their national specificity, make the author’s language more expressive and enrich the folk phraseology.